Implementation of Restorative Justice in Settlement of Criminal Actions in the Criminal System in Indonesia - Syarifuddin, Syarifuddin; Purba, Indra Gunawan; Putra, Panca Sarjana (JURNAL AKTA, 2024)
Resolving several years of criminal offenses using a "restorative justice" mechanism has been hotly discussed recently. Restorative justice or restorative justice is the process of resolving criminal acts. This criminal problem resolution model involves all parties to find justice and restore the situation between the perpetrator and the victim. One of the functions of law is as "a tool of dispute settlement", various disputes can occur in society. As for the ways of resolving disputes in a society, some are resolved through formal institutions called courts. Resolving criminal acts through restorative justice is carried out from the level of investigation and investigation at the police to the prosecutor's office. These two law enforcement agencies have regulated the process and procedures for resolving criminal acts through restorative justice mechanisms. So it is hoped that this settlement model can reduce the number of cases handled by the courts, as well as reduce the burden of state costs for resolving criminal acts. Restorative justice is regulated in the Republic of Indonesia State Police Regulation Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice and Article 1 number 1 of the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. In these two regulations, the resolution of criminal cases by prioritizing restorative justice emphasizes restoration to its original state and a balance of protection and interests of victims and perpetrators of criminal acts that is not oriented towards retribution. This is an effort to reform the criminal justice system in order to realize the goals of just law. There are several criminal justice system models in the world, Control Criminal Model, Doe process of law Model and Family model, of course this justice system will be able to determine what resolution is appropriate to the criminal justice system, which is closer to restorative justice is the family model, a family approach resolving criminal cases by deliberation and consensus as intended by the fourth principle of Pancasila. A justice system with a family model involving all parties accommodates the interests of all parties, so that the original situation is restored after the case between the perpetrator and the victim. Basically, the model for resolving criminal cases outside of court, which carries the spirit of restorative justice, began to be implemented in the mid-1970s. One model for resolving criminal cases outside of court based on restorative justice is the Victim Offenders Mediation (VOM) program. The VOM program was first implemented in 1970 in North America and Europe such as Norway and Finland. VOM is a process that provides the victim's willingness as the subject of crime and violence to meet with the perpetrator, in a safe and orderly atmosphere with the aim of making the perpetrator directly responsible in the form of compensation to the victim.